Вплив нацистської пропаганди на духовне життя населення України (технології, механізми та ефективність) - Грідіна, І.М. (Інститут історії України НАН України, 2009)
The results of influence Nazi propaganda of spiritual life of Ukrainian people are unmasked in the article. Mechanism and means of ideological and psychological treatment of different categories of civil population are determined there. Reasons of failure propaganda actions of Nazi power are analyzed.